Pembelajaran Bahasa Arab Berbasis Media iPAD (i-Learning) - Koderi Koderi (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
ABSTRACT The information technology plays an urgent role in our everyday life and in the practice of education as well. When it is well-planned and prepared, it has effective functions as the media of learning. Therefore, for the sake of making an active and dynamic process of learning and accomplishing the learning objectives, the Arabic lecturers/teachers must create an interesting, inovative, effective and creative learning practices. The technology, media of learning, as well as learning strategy the lectures/teachers take and implement will seriousely influence the output of students’ learning. Electronic Learning and i-learning (iPad learning) are two medias of Arabic learning that use internet in learning process. If it is well-prepared it will automatically raise the learning output. Keywords: Teknologi, Informasi, Media, Pembelajaran, Internet, bahasa Arab